Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1590/1414-431x20186693
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide modulates ATP-evoked currents in mouse Leydig cells

Abstract: Testosterone synthesis within Leydig cells is a calcium-dependent process. Intracellular calcium levels are regulated by different processes including ATP-activated P2X purinergic receptors, T-type Ca2+ channels modulated by the luteinizing hormone, and intracellular calcium storages recruited by a calcium-induced calcium release mechanism. On the other hand, nitric oxide (NO) is reported to have an inhibitory role in testosterone production. Based on these observations, we investigated the interaction between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…An interaction between the nitrergic and purinergic systems seems to exist in LCs. In fact, recently, it has been shown that basal NO production in LCs changes the adenosine triphosphate (ATP)-evoked currents and that extra NO modulates the current through a mechanism involving the NO/cGMP signaling pathway (22).…”
Section: Role Of Cyclic Nucleotides and Pdes In T Production And Penimentioning
confidence: 99%
“…An interaction between the nitrergic and purinergic systems seems to exist in LCs. In fact, recently, it has been shown that basal NO production in LCs changes the adenosine triphosphate (ATP)-evoked currents and that extra NO modulates the current through a mechanism involving the NO/cGMP signaling pathway (22).…”
Section: Role Of Cyclic Nucleotides and Pdes In T Production And Penimentioning
confidence: 99%
“…One study showed that NO neither increased cGMP production nor modified cyclic adenosine monophosphate (cAMP) production, but alternatively, directly inhibited the cytochrome P450 enzyme family (25,26), which catalyzed several critical reactions during testosterone synthesis. In contrast, another study reported that NO critically elevated cGMP levels, which in turn blocked LH-modulated ATPevoked Ca 2+ currents required for testosterone synthesis (27,28). Interestingly, NO inhibited autophagy via complex inhibitory effects on JNK1/Bcl-2/Beclin 1 and IKK/AMPK/TSC2 pathways (39).…”
Section: Discussionmentioning
confidence: 97%
“…Nitric oxide (NO) is an important member of reactive oxygen species. Although physiological levels are required for testis function (21)(22)(23)(24), high NO concentrations can inhibit LC steroidogenesis; mechanisms inhibiting the cytochrome P450 enzyme family (25,26) or depressing NO/cyclic guanosine monophosphatec (cGMP) signaling to impair ATP-evoked Ca 2+ currents (27,28) have been suggested. NO is generated by oxidizing L-arginine to L-citrulline via NO synthases (NOSs), which constitute three isoforms: neuronal NOS (nNOS or NOS1), inducible (iNOS or NOS2), and endothelial (eNOS or NOS3) (29).…”
Section: Introductionmentioning
confidence: 99%